Criminal Liability of Legal Persons According to Albanian Judicial Practice - Karini, Lulzim; Buxhuku, Gjon (European Scientific Journal, ESJ, 2026)
The work addresses the criminal liability of legal persons in Albanian criminal law, aiming for a balanced analysis of the normative framework and its application in judicial practice. The study begins with an examination of the provisions of the 1995 Criminal Code, which laid the foundations for the criminal liability of legal persons, and continues with an analysis of Law No. 9754/2007, which is a lex specialis in this field in Albania. The work primarily focuses on the practice of the Supreme Court, particularly analyzing the conditions under which a criminal offense is considered committed in the name and for the benefit of a legal person, the role of representatives and governing bodies in establishing the link between individual acts and the criminal liability of the subject, and the criminal sanctions applied by courts, including both primary and supplementary penalties. This study is based on a doctrinal legal analysis combined with a case-study approach. In this context, the research examines primary legal sources, including the provisions of the Criminal Code and Law No. 9754/2007 “On the Criminal Liability of Legal Persons”, together with selected decisions of the Supreme Court and the Constitutional Court. Particular attention is paid to the way in which these legal provisions have been interpreted and applied in judicial practice, highlighting both the convergences and the discrepancies that emerge between legal doctrine and its practical implementation. In conclusion, the study critically evaluates the effectiveness of the current legal framework and judicial practice. It identifies specific issues and emphasizes the need for clarification and improvements in how courts address the criminal liability of legal persons, as well as legislative reforms.